2020
DOI: 10.7322/jhgd.v30.9958
|View full text |Cite
|
Sign up to set email alerts
|

Envenenamentos ofídicos em uma região da Amazônia Ocidental Brasileira

Abstract: Introdução: Os acidentes ofídicos são um problema de saúde pública e são considerados emergências clínicas, motivo este que torna os estudos em regiões de grande incidência muito importantes. Objetivo: Descrever os aspectos clínicos e epidemiológicos de pacientes vítimas de acidentes ofídicos em uma região da Amazônia Ocidental, Brasil.  Método: Trata-se de um transversal, retrospectivo e documental de abordagem quantitativa, no período de 2015 a 2016, realizado no Hospital Regional do Juruá, local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 29 publications
0
4
0
18
Order By: Relevance
“…Do total de ocorrências com serpentes peçonhentas (n=2.840), 78% eram do gênero Bothrops, enquanto 2% eram do gênero Lachesis, seguido de Crotalus (1%) e por fim, o gênero Micrurus (n=3). O alto índice de acidentes com gênero Bothrops, está de acordo com o padrão relatado no Brasil nos últimos anos (Silva, et al, 2019;Machado, 2018), e corrobora com pesquisas similares da região amazônica (Silva, et al, 2016;Melo & Maqui, 2020;Câmara, et al, 2020) e demais localidades brasileiras (Barreto, et al, 2010;Cheung & Machado, 2017;Matos & Ignotti, 2018).…”
Section: Resultsunclassified
“…Do total de ocorrências com serpentes peçonhentas (n=2.840), 78% eram do gênero Bothrops, enquanto 2% eram do gênero Lachesis, seguido de Crotalus (1%) e por fim, o gênero Micrurus (n=3). O alto índice de acidentes com gênero Bothrops, está de acordo com o padrão relatado no Brasil nos últimos anos (Silva, et al, 2019;Machado, 2018), e corrobora com pesquisas similares da região amazônica (Silva, et al, 2016;Melo & Maqui, 2020;Câmara, et al, 2020) e demais localidades brasileiras (Barreto, et al, 2010;Cheung & Machado, 2017;Matos & Ignotti, 2018).…”
Section: Resultsunclassified
“…Some Brazilian studies in Brazil have also proposed to assess the time from snakebite to patient care [ 14 , 15 ]. However, these are local studies starting from a casualty base, and their various outcomes are observed, considering specific small-scale analysis units.…”
Section: Discussionmentioning
confidence: 99%
“…Few materials have been found in Brazil and international literature. Snakebite accidents and therapeutic care were recently analyzed in municipalities like Vassouras (RJ) [ 14 ] and Cruzeiro do Sul (AC), in the Brazilian Amazon [ 15 ]. Although they did not directly highlight geographic accessibility, they addressed the conditions for obtaining treatment in the respective municipalities.…”
Section: Introductionmentioning
confidence: 99%
“…The state of Tocantins maintains the national epidemiological standard for snakebite accidents, with accidents predominating for rural workers, with the lower limbs being the most affected (FEITOSA et al, 2015;LEOBAS et al, 2016). These accidents are aggravated by the increase in time between the accident and the start of treatment, which is more frequent in rural accidents, due to the distance and difficulty of commuting to the treatment units (GUTIÉRREZ et al, 2011;FEITOSA et al, 2015;LEOBAS et al, 2016;CÂMARA et al, 2020). In the state of Tocantins, patients treated in the first hour after the accident represented 24% of the notifications (1640 bothropic accidents), a percentage lower than that observed in Brazil (27% of bothropic accidents).…”
Section: Introductionmentioning
confidence: 99%